APPLICABILITY OF GLOBAL MANAGEMENT THEORIES TO SMALL AND MEDIUM ENTERPRISE DEVELOPMENT IN UZBEKISTAN (International journal of artificial intelligence, 2026)
This article examines the extent to which five widely recognised management frameworks — Michael Porter's competitive advantage model, Geert Hofstede's cultural dimensions system, Douglas McGregor's Theory X–Y, the Kaplan–Norton Balanced Scorecard (BSC) methodology, and Lean Management — can be meaningfully applied to the small and medium enterprise (SME) sector in the Republic of Uzbekistan. Drawing on a mixed methodological approach that integrates quantitative and qualitative analysis, the study uses empirical data spanning 2022–2024 to assess the degree of compatibility between these international management paradigms and Uzbekistan's distinct economic, cultural, and institutional landscape. The central finding is that wholesale transfer of global management theories without adaptation yields limited results; by contrast, when these theories are contextualised and calibrated to local realities, they generate tangible improvements in organisational effectiveness. The article also proposes practical policy recommendations for strengthening management capacity within Uzbekistan's SME sector, expanding financial inclusion, and accelerating digital transformation.